Study of Income Comparison on Potato Farmers Between Panenmart's Partner and Non-Partner - Farizah Dhaifina Amran; Tsalis Kurniawan Husain; Andi Azrarul Amri (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2020)
The supply chain has become a problem in the trade of agricultural products. The farmers still got low prices while the price at the end consumer is high. Panenmart is there to help improve the welfare of farmers, especially horticultural farmers in South Sulawesi by establishing appropriate food prices and sustainable supply. The objectives of this study are: 1) To identify the factors that determine the decisions of potato farmers in Kanreapia Village, Gowa Regency in partnering with Panenmart. 2) To analyze income differences between potato farmers in Kanreapia Village, Gowa Regency in partnering with Panenmart. The research was carried out in Kanreapia Village, Gowa Regency because it is a vegetable producing region with several farmers partnering with Panenmart. The number of respondents used was 40 people, which are 20 Panenmart’s farmers partner and 20 of the non-partner. The results found that 1) The factors that determine the decision of potato farmers in Kanreapia Village to partner with Panenmart are the age and the farmers’ institution. 2) There is no significant difference in income between both groups.